2013
DOI: 10.1186/1756-3305-6-290
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of ND5 gene of mtDNA in populations of Anopheles sinensis (Diptera: Culicidae) malaria vector in China

Abstract: BackgroundAnopheles sinensis is a principal vector for Plasmodium vivax malaria in most parts of China. Understanding of genetic structure and genetic differentiation of the mosquito should contribute to the vector control and malaria elimination in China.MethodsThe present study investigated the genetic structure of An. sinensis populations using a 729 bp fragment of mtDNA ND5 among 10 populations collected from seven provinces in China.ResultsND5 was polymorphic by single mutations within three groups of An.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
2
18
0
1
Order By: Relevance
“…It was obvious that the YN population of An. sinensis was relatively unique in this study as in other reports [16, 46]. The finding also reported that there was a great difference between YN and other populations in the pyrethroid resistance mechanism [47, 50].…”
Section: Discussionsupporting
confidence: 68%
“…It was obvious that the YN population of An. sinensis was relatively unique in this study as in other reports [16, 46]. The finding also reported that there was a great difference between YN and other populations in the pyrethroid resistance mechanism [47, 50].…”
Section: Discussionsupporting
confidence: 68%
“…The genetic diversity results, with all Pi values being less than 0.01, indicate that S. erinaceieuropaei isolates in eastern China have low genetic variation (Neigel and Avise, 1993). Generally, the results of pairwise F ST values showed that there is moderate-to-high genetic differentiation within different populations (F ST > 0.15), indicating that the gene flow among these S. erinaceieuropaei populations has probably been interrupted over the long term (Balloux and Lugon-Moulin, 2002;Makhawi et al, 2013;Zhao et al, 2013). Under the assumption of neutrality, a population expansion produces a negative value of Tajima's D and Fu's F S tests (Tajima, 1989;Fu, 1997); therefore, the results of neutrality tests support the possible population expansion in S. erinaceieuropaei from eastern China.…”
Section: Discussionmentioning
confidence: 96%
“…However, the main vector for P. vivax is An. sinensis in mainland China [ 43 ]. It is evident that the development of An.…”
Section: Discussionmentioning
confidence: 99%